PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN (Studi Kasus pada PT AKR Corporindo Tbk) - Mohammad Makinun Amin Ardiansyah; Diana Juni Mulyati; IGN Anom Maruta (Prodi Agroindustri Universitas 17 Agustus 1945 Surabaya, 2023)
Competition in the wider business world makes a company try to improve the company's financial quality. One way that can be done to improve the company's financial quality is through increasing the prosperity of ownership or shareholders. The existence of shareholders is very influential on the survival of the company. The research aims to determine and analyze the effect of Working Capital on Company Profitability Case Study at PT AKR Corporindo Tbk. This study uses quantitative research. The sampling technique used is the Case Study Technique and Documentation Technique. Data from this study are in the form of PT AKR Corporindo Tbk's financial reports for the 2018-2022 period. Determination of this sample using the Wibisono formula and obtained data from a total of 20 samples. The data analysis technique used in this study is Simple Linear Regression Analysis. Based on the results of research conducted by researchers with the title